2011
DOI: 10.1371/journal.pone.0019090
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ATF2 Function Leads to Cranial Motoneuron Degeneration during Embryonic Mouse Development

Abstract: The AP-1 family transcription factor ATF2 is essential for development and tissue maintenance in mammals. In particular, ATF2 is highly expressed and activated in the brain and previous studies using mouse knockouts have confirmed its requirement in the cerebellum as well as in vestibular sense organs. Here we present the analysis of the requirement for ATF2 in CNS development in mouse embryos, specifically in the brainstem. We discovered that neuron-specific inactivation of ATF2 leads to significant loss of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 65 publications
1
29
1
Order By: Relevance
“…Loss of ATF2 function in murine models A number of somatic and tissue-specific knockout mouse models have been used to examine the effects of loss of ATF2 function. The targeted disruption of the Atf2 gene, inducing complete somatic loss of ATF2, results in postnatal lethality that is associated with severe respiratory defects and meconium aspiration syndrome (Ackermann et al, 2011;Maekawa et al, 1999). In this murine model, the reduced levels of PDGFRa protein and cytotrophoblast cell populations that are detected in the knockout placenta are attributed to neonatal respiratory distress and lethality.…”
Section: Regulation Of Atf2 Protein Stabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Loss of ATF2 function in murine models A number of somatic and tissue-specific knockout mouse models have been used to examine the effects of loss of ATF2 function. The targeted disruption of the Atf2 gene, inducing complete somatic loss of ATF2, results in postnatal lethality that is associated with severe respiratory defects and meconium aspiration syndrome (Ackermann et al, 2011;Maekawa et al, 1999). In this murine model, the reduced levels of PDGFRa protein and cytotrophoblast cell populations that are detected in the knockout placenta are attributed to neonatal respiratory distress and lethality.…”
Section: Regulation Of Atf2 Protein Stabilitymentioning
confidence: 97%
“…Neuronal-specific deletion of Atf2, mediated by nestin-driven Cre, results in embryonic cranial motor neuron degeneration, specifically in the hypoglossal, abducens and facial nuclei regions (Ackermann et al, 2011). In terms of disease models, work from our laboratory has demonstrated that the melanocyte-specific expression of a transcriptionally inactive ATF2, mediated by tyrosinase-driven Cre, is sufficient to block melanoma development in the Nras (Q61K) ::Ink4A 2/2 (Ink4A is also known as Cdkn2a) murine melanoma model (Shah et al, 2010).…”
Section: Regulation Of Atf2 Protein Stabilitymentioning
confidence: 99%
“…ATF2 is ubiquitously expressed and the gene is required for normal development (3, 5). Complete loss of ATF2 leads to early post-natal lethality characterized by meconium aspiration syndrome (6), whereas mutations that compromise ATF2 function lead to early mortality with incomplete penetrance and an array of abnormalities, most notably neurological defects, in surviving animals (79). ATF2 therefore plays an important role in signaling during early development.…”
Section: Atf2 Genementioning
confidence: 99%
“…Neuron-specific inactivation of ATF2 led to a significant loss of motor neurons in the brainstem; these developed normally but were unable to survive undergoing apoptosis. In this study it was proposed that ATF2 is required for correct motor neuron differentiation, and that it might achieve this by limiting the activity of stress kinases [122]. DKO mice for CREB and cyclic AMP response element modulatory protein (CREM) also show extensive neuronal loss as a result of increased apoptosis during neuronal development [121].…”
Section: Disruption Of Noncanonical Components Such As the Transcripmentioning
confidence: 99%